Islamic Education Learning Management With An Integrated Project-Based Model Rahmatan Lil Alamin - Jannah, Miftakhul; Maulidia, Alfi; Shohifur Rizal, Moh. Ahsan (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
The article discusses effective management strategies to overcome challenges in Islamic education management The importance of learning models in education to produce effective learning experiences, especially in developing skills. Project-based learning models are emerging as an innovative solution, helping students be creative, critical, and collaborative, and develop higher-order thinking skills. The research method used is a qualitative literature review by collecting data from various sources, such as books, journals, theses, and other scientific works. The integration of the Rahmatan Lil Alamin profile has a positive impact on student character development, spiritual and material balance, tolerance, openness, student empowerment, development of life skills, psychological and emotional well-being, respect for the environment, participation in society, and the formation of Islamic identity. Thus, project-based PAI learning becomes an effective tool in shaping student character according to the concept of rahmatan lil alamin. It is hoped that this implementation can create a generation that will bring grace to the entire universe.